Multi-metal composite material as well as preparation method and application thereof

By using liquid metal auxiliary reducing agents and carbon nanomaterials in the preparation of multivariate alloys, the problems of production difficulties and insufficient performance in traditional methods are solved, and the efficient preparation of multivariate metal composite materials is achieved, and its electromagnetic wave absorption/shielding performance is significantly improved.

CN119387582AInactive Publication Date: 2025-02-07HUNAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411548350.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The traditional multi-alloy preparation method has problems such as element segregation, difficulty in phase interface control, high cost, large energy consumption, uneven coating, and overheating or supercooling of the treatment process. The existing electromagnetic wave absorption and shielding materials have shortcomings in performance and thickness.

Method used

Liquid metal is used as auxiliary reducing agent, by uniformly dispersing the metal salt powder and carbon nanomaterial in the solvent, induced reactions by mechanical force, and then separation of the product by physical or chemical methods to obtain a loaded multi-metal composite material.

Benefits of technology

It realizes efficient preparation of multi-metal composite materials under mild conditions, with simple process and low cost, can adjust the electromagnetic parameters of the material, significantly improve the electromagnetic wave absorption/shielding performance, and prepare wave absorbing materials with excellent performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119387582A_ABST
    Figure CN119387582A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a multi-element metal composite material, and belongs to the technical field of multi-element alloy material preparation. The invention particularly relates to various metal salts and carbon nanomaterials, liquid metal is used as a reaction medium, electron transfer and co-reduction in-situ deposition are triggered by utilizing the electron-rich property and active electrochemical behavior of the liquid metal, and therefore simple, rapid and mild preparation of the multi-metal composite material is achieved. Electromagnetic parameters of the multi-element metal composite material are optimized by adjusting the type and proportion of the metal salt and the proportion of the metal salt to the carbon nanomaterial, and the electromagnetic wave absorption / shielding effect of the multi-element metal composite material is improved. The prepared multi-metal composite material is simple in process, mild in reaction condition, short in reaction period and suitable for large-scale industrial production. Electromagnetic parameters can be flexibly adjusted by changing the types and proportions of various materials, personalized adjustment of product characteristics is achieved, and commercialized production is expected to be achieved in the field of electromagnetic wave absorption / shielding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of multi-component alloy material preparation, and in particular to a multi-component metal composite material and a preparation method and application thereof. Background Art

[0002] With the continuous progress of modern science and technology, human society's demand for high-performance materials is growing. Multi-element alloy materials can significantly improve the mechanical properties, corrosion resistance, high-temperature stability, magnetism and other properties of materials by combining the physical and chemical properties of different metals, and play a key role in aerospace, intelligent manufacturing, precision instruments and other fields. At the same time, its adjustable element types / proportions give it flexible active sites and tunable electromagnetic parameters, showing great potential in the fields of catalysis, electromagnetic wave absorption and shielding. Especially in the context of the rapid development of electronic information technology, the excellent electromagnetic properties of multi-element alloys are of great significance to improving the performance of electronic equipment and protecting the human body from electromagnetic radiation.

[0003] However, although the traditional methods for preparing multi-component alloys, such as smelting, powder metallurgy, mechanical synthesis, electrodeposition and heat treatment, can meet the needs of material preparation to a certain extent, there are still some problems to be solved. For example, the smelting method has the problem of element segregation and difficulty in controlling the phase interface during the smelting process; the powder metallurgy method and mechanical synthesis method have the problems of high cost and high energy consumption; the electrodeposition method has the problem of uneven coating; and the heat treatment method has the problems of overheating and overcooling during the treatment process. These problems limit the further development and application of multi-component alloy materials.

[0004] On the other hand, with the popularization of electronic devices and the development of wireless communication technology, the interference and radiation problems of electromagnetic waves are becoming increasingly serious. Excessive exposure to electromagnetic waves will not only cause harm to human health, but also affect the normal operation of electronic equipment. Therefore, the development of efficient electromagnetic wave absorption and shielding materials is urgent. At present, new materials such as graphene, carbon nanotubes, conductive polymers, and magnetic materials have become a hot spot in the research of electromagnetic wave absorption and shielding materials due to their unique physical and chemical properties. However, existing materials still have shortcomings in electromagnetic wave absorption performance, thickness, etc. Multi-element alloy materials have tunable elemental composition and microstructure, which can finely control the electromagnetic properties of materials and are regarded as an important type of electromagnetic wave absorption and shielding materials.

[0005] In order to solve the above problems, the present invention proposes a multi-component metal composite material and a preparation method and application thereof. Summary of the invention

[0006] 1. Technical Problems to be Solved by the Present Invention

[0007] The purpose of the present invention is to propose a method for preparing a multi-component metal composite material to solve the problems raised in the background technology. The present invention not only avoids the problems existing in the traditional preparation method, realizes the simple, rapid, efficient and controllable preparation of the multi-component alloy composite material, but also can design and optimize the material composition according to the needs of electromagnetic wave absorption and shielding, and provides new ideas and methods for the development of electromagnetic wave absorption or shielding materials, which is of great significance to promoting the development of this field.

[0008] 2. Technical solution

[0009] To achieve the above object, the present invention provides the following technical solutions:

[0010] A method for preparing a multi-element metal composite material comprises the following steps:

[0011] S1. dissolving metal salt powder in a solvent and uniformly dispersing carbon nanomaterials therein to obtain a uniform dispersion;

[0012] S2, adding liquid metal to the dispersion prepared in S1, and inducing a reaction by mechanical force;

[0013] S3. Use physical or chemical methods to promote the stratification of liquid metal and the reaction products in S2, separate the products, and then wash and dry them to obtain a multi-metal composite material loaded with carbon nanomaterials.

[0014] Furthermore, the metal salt powder in S1 includes, but is not limited to, a combination of two or more metal salts of different elements selected from chlorides, sulfates, nitrates, and acetylacetonates of iron, cobalt, nickel, platinum, rhodium, gold, silver, molybdenum, indium, germanium, tin, lead, tungsten, palladium, and iridium; the solvent is at least one of water, methanol, ethanol, propanol, isopropanol, ethylene glycol, glycerol, or polyethylene glycol; and the carbon nanomaterial is at least one of graphene, carbon nanotubes, carbon fibers, and carbon nanobelts.

[0015] Furthermore, the concentration of the metal salt in the dispersion prepared in S1 is 0.001-1 mol / L, and the mass ratio of the carbon nanomaterial to the metal salt is (0.001-5):1.

[0016] Furthermore, the liquid metal in S2 is Ga-based liquid metal or a low melting point alloy; the mechanical force is generated by at least one of ultrasonic, shearing, oscillation, and ball milling mechanical operations, and the action time is 0.1 to 120 minutes.

[0017] Furthermore, the mass ratio of the liquid metal to the metal salt in S2 is (1-20):1; preferably, a shearing operation is used to induce the reaction, and the shearing speed is 200-15000 rpm and the shearing time is 10-1000 s; after the shearing is completed, the mixed solution is magnetically stirred for 5-100 min.

[0018] Furthermore, the physical method for promoting stratification in S3 is at least one of filtration, centrifugal separation, and decantation; and the chemical method is at least one of oxidation bubbling, electrochemistry, and thermochemistry.

[0019] Furthermore, the reaction product is preferably separated from the liquid metal by decantation, the separated product is washed with deionized water, and then dried in an oven to obtain a multi-component alloy composite material; wherein the drying temperature is 30 to 120° C. and the drying time is 1 to 15 hours.

[0020] Furthermore, at least two of the metal elements participating in the reaction are compounded together, and all the metals participating in the reaction are evenly distributed on the carbon nanomaterial to form a multi-metal composite material.

[0021] The invention further protects a multi-metal composite material prepared by the method.

[0022] Further protection is provided for the application of the multi-metal composite material as mentioned above in electromagnetic wave absorption and shielding.

[0023] 3. Beneficial effects

[0024] (1) The present invention provides a method for preparing a multi-metal composite material, which uses liquid metal as an auxiliary reducing agent to achieve efficient preparation of the multi-metal composite material under mild conditions. The process conditions are mild, the process is simple, the cost is low, and large-scale industrial production can be achieved.

[0025] (2) When preparing the multi-component metal composite material, the metal salt raw materials used in the present invention can be freely selected and combined. By adjusting the types and proportions of different metal salts and the mass ratio of metal salts to carbon nanomaterials, the electromagnetic parameters of the multi-component metal composite material can be adjusted, the electromagnetic wave absorption / shielding performance of the composite material can be improved, and an absorbing material with excellent electromagnetic wave absorption / shielding performance can be prepared. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is an X-ray diffraction pattern of the multi-component metal composite material prepared in Example 1 of the present invention;

[0027] Figure 2 The scanning electron microscope image of the multi-element metal composite material prepared in Example 1 of the present invention and the corresponding element distribution mapping image of the energy dispersive spectrometer;

[0028] Figure 3 is a reflection loss diagram of the multi-element metal composite material prepared in Example 1 of the present invention;

[0029] Figure 4 is a reflection loss diagram of the multi-element metal composite material prepared in Example 2 of the present invention;

[0030] Figure 5 This is a reflection loss diagram of the multi-metal composite material prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings.

[0032] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0033] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0034] Embodiment 1:

[0035] This example provides a method for preparing a GaPt / FeCoNiRu-CNTs multi-metal composite material, which specifically includes the following steps:

[0036] S1, FeCl with a molar mass ratio of 1:1:1:1:1 3 6H 2 O、CoCl 2 、NiCl 2 , K 2 PtCl 4 and RuCl 3 ·3H 2 0.05 mmol of each O was mixed with 20 mg of acidified carbon nanotubes (CNTs), 25 mL of water was added, and ultrasonic dispersion was performed for 5 min.

[0037] S2. Add 0.05 g of liquid metal gallium to the dispersion, use a high-speed shear emulsifier, and rapidly shear for 30 seconds at a rate of 10,000 rpm. After shearing, use a magnetic stirrer to stir at a speed of 1,000 rpm for 10 minutes.

[0038] S3. KOH is added to the mixed solution to separate the product from the liquid metal. The upper layer solution containing the product is collected by decantation, and the solution is filtered. The obtained solid matter is washed with deionized water for 3 times, and then placed in a 60°C oven to dry for 2 hours to obtain the product. The Ga in the lower layer solution left by the decantation method is directly recycled.

[0039] The phase composition of the prepared multi-metal composite material was analyzed using an X-ray diffractometer produced by Bruker, Germany. Figure 1 As shown, the results show that GaPt alloy is formed, and the elements of iron, cobalt, nickel and ruthenium are highly dispersed and in an amorphous state without forming a clear crystal structure.

[0040] The S-4800 scanning electron microscope was used to test the morphology and size of the prepared materials. Figure 2 As shown, obvious metal particle loading can be seen, and the particles are evenly distributed and of uniform size, proving that the multi-metal composite material was successfully synthesized.

[0041] The prepared multi-metal composite material was mixed with paraffin in a mass ratio of 1:1 and pressed into concentric rings with an inner diameter of 0.3 mm and an outer diameter of 0.7 mm. The electromagnetic parameters of the material were tested using the coaxial method using the concentric rings. Figure 3 The reflection loss diagram of the multi-metal composite material prepared by the example of the present invention is shown in FIG. Figure 3 It can be seen that the multi-metal composite material has obvious electromagnetic wave absorption performance, the maximum reflection loss reaches -22.1dB, and the effective absorption bandwidth can cover the S band, C band and X band.

[0042] Embodiment 2:

[0043] This example provides a method for preparing a FeCoNiCu-RGO multi-metal composite material, and the specific preparation method includes the following steps:

[0044] S1, FeCl with a molar mass ratio of 1:1:1:1 3˙ 6H 2 O、CoCl 2 、NiCl 2 and CuCl 2 0.5 mmol of each was mixed with 20 mg of reduced graphene oxide (RGO), 25 mL of water was added, and the mixture was evenly dispersed by ultrasonic treatment for 30 min.

[0045] S2. Add 0.1 g of liquid gallium to the dispersion and use a high-speed shear emulsifier to rapidly shear for 30 seconds at a rate of 15,000 rpm. After shearing, use a magnetic stirrer to stir at a speed of 1,000 rpm for 10 minutes.

[0046] S3. The separation of the product and the liquid metal and the product treatment process are the same as in Example 1.

[0047] The prepared multi-metal composite material was mixed with paraffin in a mass ratio of 1:1 and pressed into concentric rings with an inner diameter of 0.3 mm and an outer diameter of 0.7 mm. The electromagnetic parameters of the material were tested using the coaxial method using the concentric rings. Figure 4 The reflection loss diagram of the multi-metal composite material prepared by the example of the present invention is shown in FIG. Figure 4 It can be seen that the multi-metal composite material has obvious electromagnetic wave absorption performance, with the maximum reflection loss reaching -21.5dB, and its absorption bandwidth can achieve wide absorption in the range of 2.0 to 16.5GHz by adjusting the thickness of the concentric rings.

[0048] Embodiment 3:

[0049] This example provides a method for preparing a FeCoNiCuMo-RGO multi-metal composite material, and the specific preparation method includes the following steps:

[0050] S1, FeCl with a molar mass ratio of 1:1:1 3˙ 6H 2 O、CoCl 2 、NiCl 2 , CuCl 2 and MoCl 3 0.5 mmol of each was mixed with 20 mg of reduced graphene oxide (RGO), 25 mL of water was added, and the mixture was evenly dispersed by ultrasonic treatment for 30 min.

[0051] S2. Add 0.1 g of liquid gallium to the dispersion and use a high-speed shear emulsifier to rapidly shear for 60 seconds at a rate of 10,000 rpm. After shearing, use a magnetic stirrer to stir at a speed of 1,000 rpm for 30 minutes.

[0052] S3. The separation of the product and the liquid metal and the product treatment process are the same as in Example 1.

[0053] The prepared multi-metal composite material was mixed with paraffin in a mass ratio of 1:1 and pressed into concentric rings with an inner diameter of 0.3 mm and an outer diameter of 0.7 mm. The electromagnetic parameters of the material were tested using the coaxial method using the concentric rings. Figure 5 The reflection loss diagram of the multi-metal composite material prepared by the example of the present invention is shown in FIG. Figure 5 It can be seen that the multi-metal composite material has obvious electromagnetic wave absorption performance, with the maximum reflection loss reaching -45dB, and its absorption bandwidth can achieve effective absorption of 3 to 18GHz by adjusting the thickness.

[0054] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and improved concepts of the present invention within the technical scope disclosed by the present invention, and they should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a multi-component metal composite material, characterized in that: The following steps are involved: S1. dissolving metal salt powder in a solvent and uniformly dispersing the nanomaterial therein to obtain a uniform dispersion; S2, adding liquid metal to the dispersion prepared in S1, and inducing a reaction by mechanical force; S3. Use physical or chemical methods to promote the stratification of liquid metal and the reaction products in S2, separate the products, and then wash and dry them to obtain a multi-metal composite material loaded with carbon nanomaterials.

2. The method for preparing a multi-component metal composite material according to claim 1, characterized in that: The metal salt powder in S1 includes a combination of two or more metal salts of different elements selected from chlorides, sulfates, nitrates, and acetylacetonates of iron, cobalt, nickel, platinum, rhodium, gold, silver, molybdenum, indium, germanium, tin, lead, tungsten, palladium, and iridium; the solvent is at least one of water, methanol, ethanol, propanol, isopropanol, ethylene glycol, glycerol, or polyethylene glycol; and the carbon nanomaterial is at least one of graphene, carbon nanotubes, carbon fibers, carbon nanobelts, and carbon nanocages.

3. The method for preparing a multi-component metal composite material according to claim 2, characterized in that: The concentration of the metal salt in the dispersion prepared in S1 is 0.001-1 mol / L, and the mass ratio of the carbon nanomaterial to the metal salt is (0.001-5):

1.

4. The method for preparing a multi-component metal composite material according to claim 1, characterized in that: The liquid metal in S2 is gallium-based liquid metal or a low melting point alloy; the mechanical force is generated by at least one of ultrasonic, shearing, oscillation, and ball milling mechanical operations, and the action time is 0.1 to 120 minutes.

5. The method for preparing a multi-component metal composite material according to claim 4, characterized in that: The mass ratio of the liquid metal to the metal salt in S2 is (1-20):1; when the shear operation is used to induce the reaction, the shear speed is 200-15000 rpm and the shear time is 10-1000 s; after the shearing is completed, the mixed solution is magnetically stirred for 5-100 min.

6. The method for preparing a multi-component metal composite material according to claim 1, characterized in that: The physical method for promoting stratification in S3 is at least one of filtration, centrifugal separation, and decantation; the chemical method is at least one of oxidation bubbling, electrochemistry, and thermochemistry.

7. The method for preparing a multi-component metal composite material according to claim 6, characterized in that: The reaction product is separated from the liquid metal by decantation, the separated product is washed with deionized water, and then dried in an oven to obtain a multi-component alloy composite material; wherein the drying temperature is 30-120° C., and the drying time is 1-15 hours.

8. A multi-metal composite material prepared by the method according to any one of claims 1 to 7.

9. Use of the multi-metal composite material as claimed in claim 8 in electromagnetic wave absorption and shielding.

Citation Information

Patent Citations

  • Preparation method of metal and alloy nanocrystalline

    CN110578069A

  • Multi-element metal oxide coated modified nickel-cobalt-manganese ternary positive electrode material as well as preparation method and application thereof

    CN113753972A

  • Liquid metal thermal interface material and preparation method thereof

    CN116554842A

  • Conductive material and preparation method therefor, and electronic device

    WO2021023162A1